Slow rusting resistance in pea (Pisum sativum) - SINGH, VINOD KUMAR; SRIVASTAVA, C P; CHAND, R; KUSHWAHA, C (The Indian Journal of Agricultural Sciences, 2012)
Genetic studies on pea rust was conducted to assess the nature and magnitude of gene action for slow rusting resistance in pea. Five crosses were made involving six genotypes of pea that were chosen on the basis of diversity in slow rusting traits. Data were recorded on five slow rusting traits and were subjected to the generation mean analysis. The additive types of gene action predominantly controlled the slow rusting resistance in most of the cases. Among interaction components both additive × additive (î) as well as dominance × dominance (Î) kinds of gene action was important for slow rusting resistance; duplicate type of epistasis was predominant in the expression of slow rusting resistance. To recover recombinants with enhanced level of slow rusting resistance, pedigree method of breeding has been suggested.